Odpowiedzi

2010-02-02T20:12:42+01:00
A)
4(x-2)=16
4x-8=16
4x=24
x=6

b)
4x-x+2=6-6(x-2)
4x-x+2=6-6x+12
9x=16
x=1⁷/₁₆

c)
-(x-3)=6x-(4-x)
-x+3=6x-4+4x
-11x=-7
x=7/11

d)
-x+5,6+6x=-(4,4-2x)
-x+5,6+6x=-4,4+2x
3x=-10
x=-3¹/₃
2010-02-02T20:15:46+01:00
4x-8=16 4x=8+16 4x= 24/4 x=6
4x-x+2=6-6x+ 12 3x+2= 18-6x 3x+6x=-2+18 9x=16/9
-x+3=6x-4+x -x+3=7x-4 -x-7x=-3+7 -8x=4/(-8) x= -2/4
5x+5.6=-4.4+2x 5x-2x=-5.6-4.4 3x=1.2/3 x= 0.4
Najlepsza Odpowiedź!
2010-02-02T20:16:47+01:00
A) 4(x-2)=16
4x-8=16
4x=8+16
4x=24 //4
x=6

b) 4x-x+2=6-6(x-2)
4x-x+2=6-6x+12
4x+x+6x=-2+6+12
11x=16 //11
x=16/11
x=1, 6/11

c) -(x-3)=6x-(4-x)
-x+3=6x-4+x
-x-6x-x=-3-4
-8x=-7 //(-8)
x= 7/8

d) -x+5,6+6x=-(4,4-2x)
-x+5,6+6x=-4,4+2x
-x+6x-2x=-5,6-4,4
3x=10 //3
x=10/3
x=3 1/3



tu gdzie jest np: 1 1/2
to jest jeden i jedna druga